Construction and characterization of an OmpH-deficient mutant of Pasteurella multocida strain X-73 - Thanya Varinrak (2018)
© 2018, © 2018 Houghton Trust Ltd. A capsule-defective mutant strain PBA129 of Pasteurella multocida was constructed by electroporation of phagemid containing the coding region of the antisense RNA of the ompH gene into the wild type strain X-73 (serovar A:1) of P. multocida. The pathogenicity and protective potency of the mutant against homologous and heterologous challenge in mice and chickens were characterized. Greyish colonies of the mutant, indicating lower capsule thickness, on selective dextrose starch agar were observed under an obliquely transmitted light stereomicroscope and compared to iridescent colonies of the wild type strain X-73. Strain PBA129 had lower capsule thickness than the wild type strain as observed with an electron microscope. Strain PBA129 was apparently attenuated, as mice and chickens inoculated with the bacteria at 108 CFU survived. Protection was observed in both mice and chickens inoculated with strain PBA129 upon challenge exposure to avian P. multocida strains X-73 and P-1059 (serovar A:3), respectively. In conclusion, the mutant strain PBA129 of P. multocida strain X-73 was completely attenuated, and it was possible to induce sufficient protection against avian P. multocida strains.